Catalpol decreases peroxynitrite formation and consequently exerts cardioprotective effects against ischemia/reperfusion insult. (April 2013) - Huang, Chaolian; Cui, Yongliang; Ji, Lele; Zhang, Wei; Li, Rong; Ma, Lei; Xing, Wenjuan; Zhou, Heping; Chen, Baoying; Yu, Jun; Zhang, Haifeng
<x xml:space="preserve">Abstract</x> Context: Peroxynitrite (ONOO−) formation triggers oxidative/nitrative stress and contributes to exacerbated myocardial ischemia/reperfusion (MI/R) injury. Catalpol, an iridoid glycoside, abundantly found in the roots of Rehmannia glutinosa L. that is included in the family Phrymaceae in the order Lamiales, endemic to China, was found to have neuroprotective effects. However, the effect of catalpol on MI/R injury has not been identified. Objective: This study investigated whether catalpol attenuates oxidative/nitrative stress in acute MI/R. Materials and methods: Adult male rats were subjected to 30 min of myocardial ischemia and 3 h of reperfusion and were treated with saline, catalpol (5 mg/kg, i.p., 5 min before reperfusion) or catalpol plus wortmannin (15 µg/kg intraperitoneally injected 15 min before reperfusion). Results: Pretreatment with catalpol significantly improved cardiac functions, reduced myocardial infarction, apoptosis and necrosis of cardiomyocytes after MI/R (all p < 0.05). Meanwhile, ONOO− formation was markedly reduced after catalpol treatment (3.01 ± 0.22 vs. 4.66 ± 0.53 pmol/mg protein in vehicle, p < 0.05). In addition, catalpol increased Akt and endothelial nitric oxide synthase phosphorylation, nitric oxide (NO) production, anti-oxidant capacity and reduced MI/R-induced inducible nitric oxide synthase expression and superoxide anion (·O2−) production in I/R hearts. PI3K inhibitor wortmannin not only blocked catalpol-induced Akt activation, but also attenuated all the beneficial effects of catalpol. Suppression of ONOO− formation by either catalpol or an ONOO− scavenger uric acid (5 mg/kg) reduced myocardial infarct size in MI/R rats. Discussion and conclusion: In conclusion, catalpol affords cardioprotection against MI/R insult by attenuating ONOO− formation, which is attributable to increased physiological NO and decreased ·O2− production.